Energy Use: Electricity System in West Africa and Climate Change Impact - Momodu, Abiodun Suleiman (International Journal of Sustainable Energy Planning and Management, 2018)
This article investigates a low carbon pathway, the theoretical frame for understanding the trade-offs between economic development and climate change. An already developed model - Electricity Planning-Low Carbon Development (EP-LCD) - was adapted and modified to examine the nonlinear relationship between generation adequacy and greenhouse gas (GHG) emission reduction for better targeted strategic regional intervention on climate change. Two broad scenarios - Base and LCD Option - were tested for the West African Power Pool (WAPP). The cost impact of increasing generation capacity in the LCD Option was estimated at US$1.54 trillion over a 50 year period. Achieving the goal of low carbon pathway would be largely influenced by government decision. Four strategies, in line with the Nationally Determined Contribution in Paris Agreement, were recommended. These are: a) enforced improved efficient electricity generation through increased energy efficiency that should result in increased capacity factor; b) decreased energy intensity of economic activities to result in reduced emission factor in existing plants; c) attract new investment through low tax or tax exemption to reduce cost of constructing power plants for the benefit of base-load plants; and d) subsidized cost of low-carbon fuels in the short run to benefit intermediate load plants and allow for the ramping up of low-/no-carbon fuel generation capacity. These are recommended considering the region’s specific economical and political conditions where funds are tremendously difficult to raise. Implementing these recommendations will allow the electric power industry in West Africa to contribute to achieving sustainable development path.